Diagnosis of Coronavirus using Biochemical and Hematological Methods for Patients in Anbar Governorate - Ban Hamid Khalaf1 , Qasim Khlaif Abdullah2 , Oqbah Abdul Halim3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In view of the great importance of this virus and the major health problems it causes that may reach deathand the importance of early diagnosis of this virus, which works to reduce deaths, this study came for theearly diagnosis of this virus, as we relied on biochemical and blood methods for the speed of diagnosis andthe low cost compared to the rest of the tests Where many tests were tested, including ferritin, LDH, andDi dimer, where there was a significant increase in the concentration of these tests compared to the control.No significant differences were observed between men and women. As for the hematological tests, whichincluded WBC count, Neutrophiles, Lymphocytes. There is a significant decrease in the number of whiteblood cells and lymphocytes in comparison with the control. We conclude through the study that infectionwith Corona virus increases many biochemical and hematological variables, including a significant increasein ferritin, a significant increase in LDH and Di dimer, in addition to a decrease in the total number of whiteand lymphocytes